Aqui, tudo se cria, nada se copia: um estudo etnográfico da ONG Fundação Casa Grande e a formação cultural de jovens moradores de Nova Olinda/CE - Ximenes, Márcia Maria (2014)
The current situation of Non-Governmental Organizations (NGOs) in Brazil has shown changes in the activities of these institutions in relation to their appearance in the 90s of the twentieth century. In this new context, we have formulated the central question of this research: what is the relationship between an NGO working with projects involving communication, culture and the community in which it is embedded? The NGO “Casa Grande Foundation - Memorial of the Kariri Man” emerges as our object of study. Analyze the contribution of NGOs in the cultural formation of young city dwellers is the aim of this study, which is supported by the search for specific goals as: investigate what is the conception of culture that Foundation works on projects it develops; identify how the NGO sees and portrays Cariri local culture; and understand how these young people, current participants or not of Casa Grande, realize the purpose of this organization in their cultural backgrounds and the city of Nova Olinda. The field research and discussion of concepts such as: NGO (COUTINHO, 2005; GOHN, 2000, 2004, 2010; SCHERER-WARREN, 2006), culture (CUCHE, 2002; LARAIA, 2009), dialogue between popular and mass culture (MAGNANI, 2003; OLIVEIRA, 2007), globalization (GIDDENS, 1999, 2001; HELD e MECGREW, 2001; SANTOS, 2002), and the relation between local and global (HALL, 2006) guided the research methodology for an ethnographic study (ANGROSINO, 2009; BEAUD e WEBER, 2007) from the perspective of Cultural Studies (ESCOSTEGUY, 2010; MARTÍN-BARBERO, 2003). Thus, allied to the participant observation and the field diary, essential to that methodology, research strategies as anthropological interview (GUBER, 2004), analysis of documents, videos and life stories (BERTAUX, 2005), in addition to holding a workshop on musical choice as a way of broadening of Ethnography. Research results indicate that the NGO “Casa Grande Foundation - Memorial of the Kariri Man” operates in the cultural formation of young residents of Nova Olinda, aligning itself with notions of culture, in the plural, and not only to a single concept, directing the look of it to the Cariri local culture more focused on traditional manifestations. This purpose occurs even though some productions of NGOs expand this view when they cannot hide the popular dialogue with the massive, result of globalization processes.